A experiência estética do feio nas artes pictóricas - Sulamita Fonseca Lino (2020)
This thesis is dedicated to studying ugliness in the aesthetic scope and how it relates to the pictorial arts. The starting point was the ascertainment that beauty, since Ancient times, has been accompanied by ugliness, and it was with modern times that this issue was highlighted. Despite this evidence, the debate over ugliness was never autonomous and has always been bound to the matters of beauty and the sublime. In Ancient philosophical texts, such as Aristotle’s Poetics, themes touching on the effects of observing works of art with unpleasant subjects were addressed. This first piece of evidence suggests a recurring issue on debating ugliness, since the sensible experiences aroused differ from those of beauty. This text is structured as follows: in the first part, we approach the approximation of the issues of ugliness, beauty and mimesis in Ancient times; following that, we focus the debate that occurred concerning Rosenkranz’s Aesthetic of Ugliness in the 18th and 19th centuries; finally, we look at 20th century references, such as the existing problematization of the subject in Adorno’s Aesthetic Theory; and we approximate the aesthetic experiences of ugliness and the sublime conceived in the philosophical debate over the pictorial and written works of Barnett Newman.